The stakeholders‟ involvement in the process of building and maintaining a destination brand - Antonsen, Inger Marie Nyvoll (2010)
A destination is a place that attracts visitors for a temporary stay to participate in tourism related activities or non- activities. Globalization, the increased number of travelers and the increased buying power have increased the competition between the destinations and the destinations have become more substitutable. It has been agreed that destinations can be branded as well as products and to be competitive it is getting common to brand destinations. Destination Marketing Organizations (DMOs) are responsible for the marketing of an identifiable destination. The purpose of this study is to present an exploratory study of how a destination marketing organization creates and builds a strong destination brand and how the stakeholders have been involved in the process. The study is done with a qualitative case study approach. The case study was chosen as the research method to make a detailed and intensive analysis of the research objective, in this case the destination brand of Brazil and its stakeholders.